The geriatric nutritional risk index is an effective tool to detect GLIM-defined malnutrition in rectal cancer patients - Chen, Xi-Yi; Lin, Yi; Yin, Shang-Yu; Shen, Ya-Ting; Zhang, Xi-Cheng; Chen, Ke-Ke; Zhou, Chong-Jun; Zheng, Chen-Guo (Frontiers in Nutrition, 2022)
Background: This study aimed to investigate the value of the Geriatric Nutritional Risk Index (GNRI), prognostic nutritional index (PNI), and advanced lung cancer inflammation index (ALI) scores in detecting malnutrition in patients with rectal cancer; the Global Leadership Initiative on Malnutrition (GLIM) was used as the reference criterion. Materials and methods: This study included patients with rectal cancer who underwent proctectomy. GNRI, PNI, and ALI were calculated to detect the GLIM-defined malnutrition using the Receiver operating characteristic (ROC) curves. Univariate and multivariate logistic regression analyses are used to evaluate the association between the nutritional tools and postoperative complications. Kaplan-Meier survival curves, log-rank tests, and univariate and multivariate Cox regression analyses are used to clarify the relationship between nutritional tools and OS. Results: This study enrolled 636 patients with rectal cancer. The GNRI demonstrated the highest sensitivity (77.8%), pretty specificity (69.0%), and the largest AUC (0.734). Both the GNRI < 92 and ESPEN 2015 showed good property in predicting major postoperative complications. all three nutritional tools were independent predictors of overall survival (OS). Conclusion: The GNRI can be used as a promising alternative to the GLIM and is optimal in perioperative management of patients with rectal cancer among three nutritional tools